New Approach for Developing Correlation of NSPT and Shear-Wave Velocity (Vs): Bantul Case Study - Haifani Akhmad Muktaf; Wiyono Wiyono; Biatna Dulbert Tampubolon (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.395-413Predictions of ground motion levels that, under certain conditions, may cause liquefaction require a sufficient knowledge of the underlying soil characteristics. The utilization of the seismic refraction method applies measurements of the subsurface shear-wave velocities (Vs) as a representation of the properties of stiffness and soil amplification. This study, carried out in Bantul, Yogyakarta Province, Indonesia, is conducted to determine the relationship between Standard Penetration Test N values (NSPT) and Vs by using data from eighty-eight drill sites and twenty-nine seismic reflection investigations with the statistical method, namely the Statistical Gradation Approach. The new equations, developed from a power regression analysis, are applied to all soil and eight soil types: silty sand, sand, gravelly sand, clay, silt, sandy clay, clay sand, and sandy silt. The equations, proposed to predict Vs, show a strong relationship between NSPT and Vs values, which applied to other regions with the shear-wave velocity of <300 m/sec, shallow groundwater depth, and dominant sandy soil.